Aggressive behaviors and associated factors in Chinese left-behind adolescents: a cross-sectional study - Fang Yang; Zhiyu Jin; Jing He; Bingsong Han; Xinyuan Huang; Kun Chen; Jiana Wang (BMC, 2022)
Abstract Background To examine whether the levels of aggressive behaviors and other individual and contextual variables differ between left-behind adolescents (LBA) and not left-behind adolescents (NLBA) and explore associations between aggression and other constructs among them. Methods A cross-sectional study was conducted and 4530 school adolescents aged 9-18 years in north and south of China were randomly selected. The levels of aggressive behavior, personality and family and classroom environment were compared between LBA and NLBA and also the associated factors of aggression. Results The total scores of aggressive behaviors were 6.33 ± 6.35 (Mean ± SD) in LBA and 5.78 ± 6.16 (Mean ± SD) in NLBA. Multiple linear regression models revealed that neuroticism and psychoticism were positively associated with aggressive behaviors for LBA with similar results of NLBA. Cohesion was negatively associated with aggressive behaviors, and conflict and achievement had positive effects in NLBA. Organization had a negative effect in LBA. Uncertainty and dissatisfaction had positive effects on aggression both in LBA and NLBA. Conclusion This study found a slightly higher level of aggressive behaviors in LBA comparing with NLBA. Personality was the mainly associated factor of aggression, but class-based interventions were more practical for aggressive behaviors in Chinese LBA.